Levocarnitine for pegasparaginase-induced hepatotoxicity in acute lymphoblastic leukemia. Issue 13 (9th November 2020) - Trang, Elena; Ngo, Dat; Chen, Jason; Aldoss, Ibrahim; Salhotra, Amandeep; Pullarkat, Vinod
Abstract: Pegasparaginase (PEG-Asp), commonly used in acute lymphoblastic leukemia (ALL), is associated with hyperbilirubinemia and elevated transaminases. Treatment of acute hepatotoxicity is limited to case studies reporting success with levocarnitine (LC). In a retrospective analysis, 25 ALL patients experienced Grade ≥3 hyperbilirubinemia and/or elevated transaminases following a single dose of PEG-Asp where 12 patients received LC compared to 13 patients with no intervention. Median LC dose was 50 mg/kg/day for a median of 11 days. Median values were greater in the LC group: total bilirubin 5.2 mg/dL vs 4.5 mg/dL ( p  = 0.19), AST 75.5 units/L vs. 30 units/L ( p  = 0.05), and ALT 263.5 units/L vs 47 units/L ( p  = 0.003). Time to resolution (TTR) did not significantly differ between LC and control ( p  = 0.08), however, patients on LC did resume therapy sooner ( p  = 0.17). Although significant limitations exist in the study, LC did not result in a clinically significant impact when used to treat PEG-Asp-induced hepatotoxicity.